(untitled) (Prilozi za orijentalnu filologiju, 2017)
Ali-Fehmi Džabić (1853-1918) was undoubtedly one of the more prominent personalities among Yugoslavs who wrote in Arabic. His commentaries on classical Arab poetry place him among those literary critics who, although far from his native country and writing in a foreign language, managed to master the skill to such an extent that they aroused the admiration and respect of all connoiseurs of the field. A number of papers deal with the personality and activity of Ali-Fehmi Džabić, but these are mostly papers dealing with his political activities, his leadership of the movement of the Bosnian and Herzegovinian Moslems for religious and waquf and mearif autonomy. As the leader of the movement, he travelled to Istanbul, and the Regional Government .proclaimed bim an illegal emigrant-and prevented his return home. His departure to Istanbul marked a new period in his activity as a university professor of Arabic lang age and literature, and as a compiler of anthologies and' writer of literary criticism concerning the period of classical Arab poetry. The present paper deals with his work Tilbat al-ṭālib fī šarḥ Lāmiyya Abī Tālib ·- a commentary on Abu Talib's cassida Lāmiyya.